Mamografske spremembe v dojkah po operativnih posegih in radioterapiji - Jančar, Breda (Radiology and oncology (Ljubljana), 1998)
The changes wich develop in the breast after the completed therapy of primary breast carcinoma by surgery and radiotherapy may easily be confounded with residual or a second primary carcinoma. A radiologist who is skilled in identifying post-operative and post irradiation changes on mammograms and knows well their time-related dynamics and is , at the same time, also a good expert in applying all techniques so far available in mammography, can detect a residual tumor in its most early stage. If it is treated time, at least longer survival is secured to the patients with the personal history of breastcancer or their complete remission.
Keywords: Breast neoplasms; dojke; Mammography; novotvorbe; Postoperative complications; Radiotherapy; rak (medicina); Surgery; zdravljenje